Socialization on the Dangers of Excessive Gadget Use for Early Childhood at PAUD Al-Nur Bojongsawah - Salmah Aprilia; Asri Nuriyah; Ai Herlina; Fitri Sulastri (Sekolah Tinggi Agama Islam Barumun Raya (STAI BR) Sibuhuan, 2024)
Abstract Uncontrolled gadget use among young children in Bojongsawah Village has led to negative impacts on their physical, mental, and social development. To address this issue, a socialization program was conducted at PAUD Al-Nur with the aim of increasing parents' understanding of the dangers of gadgets, providing practical guidelines for managing screen time, and offering alternative activities. The methods included interactive lectures, group discussions, Q&A sessions, and practical activities, with evaluation through pre- and post-socialization questionnaires. Evaluation results showed an increase in parental understanding from 40% to 85% and high enthusiasm for the presented material. The program successfully raised parental awareness and is expected to serve as a model for similar training in the future, contributing to the development of more effective community service programs. Keywords: Gadget, Early Childhood, Parents, Management, Impact. Abstrak Penggunaan gadget yang tidak terkontrol pada anak usia dini di Desa Bojongsawah menyebabkan dampak negatif pada perkembangan fisik, mental, dan sosial anak. Untuk mengatasi masalah ini, sosialisasi dilakukan di PAUD Al-Nur dengan tujuan meningkatkan pemahaman orang tua tentang bahaya gadget, memberikan panduan praktis untuk mengelola waktu layar, dan menawarkan alternatif aktivitas. Metode yang digunakan meliputi ceramah interaktif, diskusi kelompok, tanya jawab, dan kegiatan praktis, dengan evaluasi melalui kuesioner pra-dan-pasca sosialisasi. Hasil evaluasi menunjukkan peningkatan pemahaman orang tua dari 40% menjadi 85% dan menunjukkan antusiasme tinggi terhadap materi yang disampaikan. Kegiatan ini berhasil meningkatkan kesadaran orang tua dan diharapkan dapat menjadi model untuk pelatihan serupa di masa depan, serta berkontribusi pada pengembangan program PKM yang lebih efektif di komunitas.. Kata kunci: Gadget, Anak Usia Dini, Orang Tua, Pengelolaan, Dampak